Barriers to the adoption of open-pollinated varieties in the organic farming sector: a case study of small-scale vegetable production in France - Antier, Clémentine; Baret, Philippe V. (Frontiers in Sustainable Food Systems, 2025)
Seeds are a critical, influential element of agricultural production and sustainability. The European organic farming sector has specific standards and targets regarding its seed supply. Ideally, seeds should be grown organically, participate in the conservation of biodiversity, contribute to the autonomy of farmers, and be bred into reproducible cultivars. Inbred lines and open-pollinated varieties, along with organic heterogeneous material, fit with this criterion. In a case study of small-scale vegetable production in the South-East of France, we analyze the gap between the organic sector’s seed standards regarding reproducibility and their actual implementation when farmers buy seeds. The data were collected through a focus group and interviews of 15 farmers and seven other actors of the organic vegetable value chain. While all farmers of the sample consider open-pollinated varieties more aligned with the principles of organic agriculture and peasant farming, their perception of the operational relevance of the OP varieties currently available in seed companies’ catalogues varies and leads to contrasted varietal choices. Perceived advantages of OP varieties over hybrids include ethical and hedonic aspects along with context-specific technical advantages. On the other hand, the listed advantages of hybrid varieties are mostly about productivity, disease resistance and access to technical recommendations. This paper discusses how the technical, economic, educational, and social contexts influence farmers’ seed choices of hybrids versus open-pollinated varieties. We highlight 11 barriers to the adoption and use of open-pollinated varieties. These barriers are present in the seed market, at the farm level, as well as in the education and extension sectors. Our findings suggest that activating various levers is needed to make it more feasible for organic farmers to choose open-pollinated varieties. These findings call for further assessment of the conditions required for the adoption of reproducible varieties in a wider range of organic farming contexts across Europe.